MENANAMKAN SEMANGAT BELA NEGARA MELALUI PROGRAM “PAHLAWANKU, PAHLAWANMU” PADA ANAK PANTI ASUHAN - Nayla Trihapsari; Berta Marcelina; Cut Huriyya 'Aqila Zichra; Nandita Afra Renata; Sri Rahma Aulia; Nabil Arij Fannan; Yohanes Christiano MT; Rafinda Rahmat; Febiyola Bungas Permata; Andiny Putri Vanosha; Ripi Hamdani (STKIP Subang, 2026)
The spirit of national defense needs to be instilled from an early age to shape the character of the younger generation who have a sense of love for the homeland, nationalism, and responsibility as citizens. Children in orphanages are one group that requires strengthening national values ​​through activities that are appropriate to their characteristics. This study aims to describe the implementation of the